Studi Literatur Manajemen Laba Di Indonesia (Periode Tahun 2015 – 2024) - Yulia Yulia (LPPM Universitas Bina Sarana Informatika, 2025)
This study aims to analyze the dynamics of earnings management practices in Indonesia during the period 2015–2024 by examining the internal and external factors that influence them and reviewing the relevance of the underlying theories. Based on the analysis of 100 selected academic articles, it was found that industrial sectors with high levels of earnings management practice risk include manufacturing, property and real estate, telecommunications and infrastructure, food and beverages, and banking. The non-cyclical consumption sector shows a relatively medium risk. The earnings management phenomenon is explained through the theoretical framework of Agency, Positive Accounting, and Signaling, which describes the existence of conflicts of interest, the selection of strategic accounting policies, and the use of earnings as a signal to the market. The results of this study emphasize the importance of strengthening corporate governance and technology-based monitoring systems to mitigate earnings management risks in the future.